Extensive Reading Project using Graded Readers in a University Classroom - Ruhil Amal, Azmuddin; Amy Zulaikha, Mohd Ali; Ezihaslinda, Ngah; Zuraina, Ali; Nooradelena, Mohd Ruslim (UMP Press, 2019)
Research into Extensive Reading (ER) has a long history as an effective method in facilitating language learning for learners. One of the many approaches in conducting ER successfully is through the use of graded readers. Despite its benefits, not much attention has been given to ER using graded readers among English as a Second Language (ESL) university students in Malaysia. This study explores the influence of ER project with the use of graded readers among control (n=90) and experimental (n=125) groups of undergraduate university students enrolled in various compulsory English courses during a 14-week academic calendar. ER project was conducted to supplement learning through various in class projects. Data was collected through the use of pre- and post-tests, progress tests as well as extensive reading tests obtained through Edinburgh Project in Extensive Reading (EPER). Results indicated no significance difference among control and experimental groups for pre-tests, post-tests and extensive reading tests. These results carry important implications on pedagogical and methodological aspects of language teaching and learning, which are further discussed in the paper.